Development of Performance Technology Competency Training Model for Students of Chemical Education - Zurweni Zurweni; Affan Malik (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2022)
The free learning-campus program (MB-KM) contained in SN-Dikti 2020, is very relevant to the demands of 21st century education in order to address the challenges of learning in the global era. The MB-KM program provides opportunities for students to master various fields of science, develop creativity, capacity and other competencies related to the needs of the world of work. The results of the needs analysis show that there are still four competencies that have not been maximally mastered by students, namely: school management competencies, analytical thinking, technological novelty and science behavior with an average of 51.75%, while the other three competencies: pedagogical competence, high school chemistry science, and DIGITAL LEARNING IT competence have been very good with an average of 80.20%. Against the background, this was conducted research on the Development of Rational-Creative Performance Technology Training Model for Chemistry Education Students. This research is educational development research (Borg & Gall: 2007). The characteristic of this training model is in the form of Merdeka Learning Teacher Mover for school education. The MODEL ID used to design this training model is adapting the modified ASSURE model, while the Rational-Creative Performance Technology Training Model was developed by Zurweni & Affan Malik (2020). The results showed that the Rational-Creative Performance Technology Training Model has four synths: Innovation Intervention Orientation, Rational Exploration, Rational Technology Training and Evaluation. Evaluation and validation results and trials state that the Rational-Creative Performance Technology Training Model falls into the category of good, with field trials have not been successfully implemented due to the covid-19 pandemic. It was concluded that this Rational-Creative Performance Technology Training Model is worth using and is a new breakthrough as an alternative to enrichment in the debriefing of students who follow the PLP Program to partner schools. It is recommended to use this training model at the level of the Study Program as well as at the student debriefing enrichment session before following the introduction of the school field.